2006
DOI: 10.1007/s11144-006-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Carvone epoxidation by system “hydrogen peroxide-[Mn2L2O3][PF6]2 (L = 1,4,7-trimethyl-1,4,7-triazacyclononane)-carboxylic acid”: a combinatorial approach to the process optimization 

Abstract: Epoxidation of natural terpene (+)-carvone by the system consisting of a catalyst, oxalic acid (co-catalyst) and H 2 O 2 (70% aqueous solution; oxidant) was studied and factorial design methods were applied for the optimization of this reaction. A dinuclear manganese(IV) complex [LMn(O) 3 MnL](PF 6 ) 2 (L = 1,4,7-trimethyl-1,4,7-triazacyclononane) was used as a catalyst, and acetonitrile was employed as a solvent. An analysis by methods of the complete 2 4 factorial design showed that an increase in the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This reaction provided a mixture of stereoisomers, which shows that the size of the isoxazolinic cycle also plays a certain role in the stereospecificity of the reaction. This result is consistent with the literary data regarding the epoxidation of the terminal double bonds in dipolarophile I and II [21][22][23]. In a 200 mL erlenmeyer flack, equipped with a bromine funnel, were introduced 1.00 g of (-)-(R)-carvone (6.66 mmol) and 1.03 g of 4-chlorobenzaldehyde oxime in CHCl3 (30 mL).…”
Section: Introductionsupporting
confidence: 89%
“…This reaction provided a mixture of stereoisomers, which shows that the size of the isoxazolinic cycle also plays a certain role in the stereospecificity of the reaction. This result is consistent with the literary data regarding the epoxidation of the terminal double bonds in dipolarophile I and II [21][22][23]. In a 200 mL erlenmeyer flack, equipped with a bromine funnel, were introduced 1.00 g of (-)-(R)-carvone (6.66 mmol) and 1.03 g of 4-chlorobenzaldehyde oxime in CHCl3 (30 mL).…”
Section: Introductionsupporting
confidence: 89%
“…Some of us [70] discovered in 1998 that dinuclear manganese(IV) complex [LMn(O) 3 MnL](PF 6 ) 2 (catalyst 1a, where L is 1,4,7-trimethyl-1,4,7-triazacyclononane, TMTACN; see Scheme 1) catalyzes the oxidation of organic compounds by hydrogen peroxide if a small amount of a carboxylic acid is added to the reaction solution. Further, we demonstrated that the '1a/carboxylic acid/ H 2 O 2 ' combination in acetonitrile solution very efficiently oxidizes various organic compounds [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] (see also reviews [88][89][90][91][92][93][94]) including inert alkanes [70-76, 78, 81, 82, 85-87] to afford primarily the corresponding alkyl Scheme 1 Catalysts used in the present work hydroperoxides which are transformed in the course of the reaction into the more stable ketones (aldehydes) and alcohols. It turned out that the system oxidizes not only alkanes but also epoxidizes olefins [72, 74-76, 84, 87], transforms alcohols into ketones (aldehydes) [72,77,83] and sulfides into sulfoxides [72].…”
Section: Introductionmentioning
confidence: 96%
“…The reaction with olefins afforded the products of dihydroxylation [74] in addition to the corresponding epoxides. Alkanes [75], olefins [76], and alcohols [77] were oxidized also in the absence of acetonitrile. A relevant soluble polymer-bound Mn(IV) complex with N-alkylated 1,4,7-triazacyclononane was used as a catalyst in the H 2 O 2 oxygenation of alkanes [82].…”
Section: Introductionmentioning
confidence: 99%